Human bovine tuberculosis - remains in the differential. - MURPHY, PHILIP (My University, 2010)
Mycobacterium bovis is a pathogen of cattle. The unpasteurized milk of affected cattle is a source of infection in humans. Despite the screening of cattle and the pasteurization of milk, M bovis has not been eradicated. A high index of clinical suspicion is needed in symptomatic patients with a history of possible exposure. At risk groups include animal workers, farmers, meat packers, vets and zoo keepers. Humans are usually infected by the aerosol route. We present two cases of human bovine tuberculosis. One was a presumptive case and the second was a confirmed case. Both responded well to antituberculous therapy. In the confirmed case, there was evidence of transmission to the partner living in the same house. Rifampicin prophylaxis was given to the exposed case. The M. bovis from the confirmed case was isoniazid resistant, in addition to having the well known resistance to pyrazinamide. Isoniazid resistance has been described before in those who are immunocompromised. We describe it in an immunocompetent patient.
PUBLISHED
Keywords: Immunology; human bovine tuberculosis